2009
DOI: 10.3340/jkns.2009.45.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Instrumented Mini-TLIF and Instrumented Circumferential Fusion in Adult Low-Grade Lytic Spondylolisthesis : Can Mini-TLIF with PPF Replace Circumferential Fusion?

Abstract: consecutive patients underwent instrumented circumferential fusion (group II) at Leon Wiltse Memorial Hospital, Suwon, Korea. The mean follow-up periods were 29.7 and 26.1 months, respectively. Results : Mean visual analog scale (VAS) scores for back and leg pain decreased, respectively, from 6.98 and 6.33 to 2.3 and 2.2 in group I and from 7.38 and 6.00 to 1.7 and 1.0 in group II. Mean Oswestry disability index (ODI) improved from 51.85% to 14.4% in group I and from 60% to 9.1% in group II. In both groups, VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…In all, we included 29 papers in our review. We classified the modalities materials used for fusion according to cage or spacer type and source of graft and/or bone extender used and calculated data for each independently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, we included 29 papers in our review. We classified the modalities materials used for fusion according to cage or spacer type and source of graft and/or bone extender used and calculated data for each independently.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown TLIF to be superior to both anterior‐posterior fusion and posterior lumbar internal fixation for treating symptomatic disc degeneration, as well as a suitable procedure for correcting both isthmic spondylolisthesis and adult degenerative scoliosis. The procedure has even evolved to having a minimally invasive option that has also proven to be effective and, for some indications, even more effective than traditional TLIF. There have been numerous published reports assessing the efficacy of cage and screw placement, use of recombinant human bone morphogenetic protein 2 (rhBMP‐2) and other factors thought to contribute to successful fusion.…”
Section: Introductionmentioning
confidence: 99%
“…Le traitement du spondylolisthésis par lyse isthmique de l'adulte repose, le plus souvent, sur l'arthrodèse instrumentée de l'étage olisthésique. Celle-ci peut être obtenue via un abord postérieur par arthrodèse postérolatérale (PLF) [8,9] ou intersomatique par voie postérieure (PLIF) [8,9], par voie transforaminale (TLIF) [10,11] via un abord antérieur (ALIF) [12,13] ou par une approche combinée, antérieure et postérieure (arthrodèse circonférentielle) [14][15][16][17][18][19].…”
Section: Discussionunclassified
“…[21,22] There have been multiple authors describing MIS techniques for various indications that have shown equivalent fusion rates and functional outcomes compared with standard open procedures. [18,[23][24][25] Wang et al have reported on the successful application of MIS fusion techniques to treat adult spinal deformities. [26] In a review of 42 patients, Dhall et al [27] open group (P < 0.01).…”
Section: Minimally Invasive Spinal Surgery Lumbar Fusionmentioning
confidence: 99%